2001
DOI: 10.1089/10507250152740966
|View full text |Cite
|
Sign up to set email alerts
|

Antithyrotropin Receptor Antibody: An Update

Abstract: Numerous studies have reported the characteristics and significance concerning antithyrotropin receptor antibodies (TSHR-Abs), which cause Graves' disease and in some cases primary hypothyroidism. However, many unsolved questions concerning those antibodies remain. Here, recent developments in the study of TSHR-Abs are reviewed based on three aspects: mechanisms of TSHR-Ab production, antibody binding epitopes, and clinical TSHR-Ab assays. Mechanisms of TSHR-Ab production are discussed from five points of view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 129 publications
0
18
0
1
Order By: Relevance
“…As TRAb are considered the hall markers of GD [41,42], their persistence in the blood of patients treated with ATD may indicate on going active disease. For this reason many investigators are focused on the possible role played by TRAb as predictors of GD outcome [10-13, 20, 43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…As TRAb are considered the hall markers of GD [41,42], their persistence in the blood of patients treated with ATD may indicate on going active disease. For this reason many investigators are focused on the possible role played by TRAb as predictors of GD outcome [10-13, 20, 43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with GD, it is assumed that such antibodies stimulate receptor activity and, hence, thyroid function. However, albeit highly sensitive and specific, TBII assays do not discriminate between in vivo stimulating antibodies (responsible for GD), blocking-type antibodies (found rarely in women with Hashimoto's disease), or neutral antibodies (355). Currently available bioassays are the thyroid-stimulating antibodies (TS-Ab) assays.…”
Section: A Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Various approaches to identify the TSHR epitopes have involved in silico, in vitro, in vivo , and clinical studies, and some TSHR epitope clusters were reported (7, 8). Thyroid function is regulated by not only TRAb but also cell-mediated immunity (9). Two major regulations (central and peripheral) maintain self-tolerance (2).…”
Section: Introductionmentioning
confidence: 99%